(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
This paper presents the results of the excavation of a house built in wood, pisé and opus craticum. The area excavated (“Campo del Generale” - Costa di Sant’Andrea) is situated in the township of Calvatone in the province of Cremona. The building is part of the Roman vicus of Bedriacum. Up to date it is the only house which didn’t use brick, at least in it’s foundations and seems more like a protohistoric house rather than a traditional Roman one. It dates back to the end of the 2nd century B.C. and was inhabited until the end of the 1st century B.C. The analysis of the finds (saggio 6, 1986-1996) brings one to propose that the owners must have had strong ties to the indigenous peoples (Celts) as well as to Roman.